2015
DOI: 10.1158/1940-6207.capr-14-0193
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Skin Carcinogenesis by the β-Blocker Carvedilol

Abstract: The stress-related catecholamine hormones and the α- and β-adrenergic receptors (α- and β-AR) may affect carcinogenesis. The β-AR GRK/β-arrestin biased agonist carvedilol can induce β-AR-mediated transactivation of the epidermal growth factor receptor (EGFR). The initial purpose of this study was to determine whether carvedilol, through activation of EGFR, can promote cancer. Carvedilol failed to promote anchorage-independent growth of JB6 P+ cells, a skin cell model used to study tumor promotion. However, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 42 publications
5
62
0
Order By: Relevance
“…Previous studies have shown that the biased β‐blockers induced ERK1/2 phosphorylation in HEK‐293 cells transfected with β2‐AR . We therefore examined if carvedilol has the same property in JB6 P+ cells which was confirmed to express endogenous β2‐AR . We also evaluated EGF in term of its ability to induce ERK1/2 phosphorylation in JB6 P+ cells for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the biased β‐blockers induced ERK1/2 phosphorylation in HEK‐293 cells transfected with β2‐AR . We therefore examined if carvedilol has the same property in JB6 P+ cells which was confirmed to express endogenous β2‐AR . We also evaluated EGF in term of its ability to induce ERK1/2 phosphorylation in JB6 P+ cells for comparison.…”
Section: Resultsmentioning
confidence: 99%
“…AP‐1 is a heterodimeric complex containing c‐Jun and c‐Fos and induced AP‐1 activity is required for EGF‐induced JB6 transformation . As carvedilol, but not the unbiased β‐blocker atenolol, inhibited EGF‐mediated activation of AP‐1, we next used a dual‐luciferase reporter assay to examine the effect of biased β‐blocker alprenolol and unbiased β‐blocker metoprolol on EGF‐induced AP‐1 promoter activity. At 1 and 10 μM, alprenolol alone had no effect on AP‐1 activity, but strongly attenuated EGF‐induced activation of AP‐1 to the same level of the negative control (Figure A), However, metoprolol had no effect on EGF‐mediated AP‐1 activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In keeping with this suggestion, refractory cancer may be successfully treated with β-adrenoceptor blockers combined with chemotherapy [81], but the mechanisms of action beyond specific β-adrenoceptor subtype blockade are not evident. For example, Chang et al [82] showed that EGF-induced AP-1 transactivation: (i) remained unaffected by atenolol (a β-blocker with a very low affinity for β 3 -adrenoceptors) [54,63] at any dose tested (which is required for tumor promotion) and (2) was prevented by carvedilol (a nonselective β-blocker with a high affinity for β 3 -adrenoceptors; Table 1). The simplest interpretation of these findings may be that, apart from the β 1 / β 2 -mediated actions, some affinity for β 3 -adrenoceptors may be a conditio sine qua non for their antiproliferative actions.…”
Section: Basic Research: Lines Of Evidence Supporting the Potential Cmentioning
confidence: 99%
“…Furthermore, a recent chemical mouse skin carcinogenesis study on immunocompetent SENCAR mice demonstrated that oral or topical carvedilol, but not atenolol, exerted antitumor-promoting activity by suppressing the skin inflammation and epidermal hyperplasia [8]. Also, in an animal study modeling the pulmonary metastatic effects of surgery stress using immunocompetent F344 rats and MADB106 breast cancer cell line, non-specific β-blocker nadolol was shown to exert its antimetastitic effects in lungs by attenuating the stress-induced reduction in pulmonary-marginating natural killer cell (NK cell) numbers and individual NK cell activity [9].…”
Section: Introductionmentioning
confidence: 99%